Corporate Social Responsibility and Commercial Law: Balancing Profitability with Ethical and Legal Obligations in Modern Business Practice - Roaa Qasim Ayyal (International Journal of Law Research and Studies, 2025)
The research is based on "Corporate Social Responsibility and Commercial Law: Balancing Profitability with Ethical and Legal Obligations in Modern Business Practices."  The research mentions the importance of implementing effective CSR policies and the ways in which they are linked to the elements of commercial law. Maintaining a balance between ethical and legal obligations is required because it helps manage profitability levels. There are three case studies for Tesla, Unilever and Ikea, which conclude that for businesses, if they follow CSR strategies, then it would become convenient for them to fulfil their ethical and legal obligations without making any impact on the profitability levels. Primary data is also collected from 100 participants in the form of surveys and the level of significance is also high for businesses when they implement effective CSR strategies and modern practices. For future research, it is recommended to focus on specific business niches to cover high subjectivity.
Keywords: CSR; 3Ps; People; Planet; Profitability; Ikea; Unilever; Tesla and stakeholders